"Recognition and identification of children in preschool and school who are exposed to domestic violence". Issue 3 (3rd July 2018) - Münger, Ann-Charlotte; Markström, Ann-Marie
ABSTRCT: Although domestic violence takes place in the private domain, preschool and school professionals are confronted with its consequences in the intermediate domain between home and school when they encounter children who have been exposed to violence. This article investigates whether and how Swedish professionals in pre/school identify children who are exposed to domestic violence. The results show that pre/school professionals argue that they do not have enough knowledge about the phenomenon or about how to identify the symptoms or signals that emerge from family violence. However, most of these professionals talk about their experience in identifying different factors, both known and unknown, that are important in the process of recognizing children who have been exposed to domestic violence. Even though they find it important to identify and support these children, some professionals have difficulty connecting the issue of witnessing violence with child abuse. In addition, the question of whether and how children who have been exposed to domestic violence are perceived as included in the school's educational duties seems to be an important issue affecting the staff's readiness to respond to signals and symptoms.